JURIDIC ASPECTS OF THE DEVELOPMENT OF THE SEMPUANA HOLY WATER SPRING AS A TOURISM ATTRACTION IN DALUNG VILLAGE, BADUNG - I Putu Agus Suarsana Ariesta (Warmadewa Press, 2022)
One of the sacred springs/bejis that attracts attention for research is the Beji Sempuana, which is used by the local village community in the process of spiritual purification, generally this process is carried out before starting religious ceremonies such as Piodalan in the area of Pura Dalem Nataran Tegal Jaya, Dalung or mass burning of corpses (Ngerit). This Beji is located on the border of the Sempuana River which needs to be preserved due to the conversion of the surrounding land. This study aims to examine the legal basis for the development of a site into a tourist attraction. The method used in this study, namely observation to the object of research, interviews and documentation. Interviews were conducted with community leaders and local residents. The data analysis technique used in this study is a qualitative descriptive method, which provides a review of the interpretation or meaning of the data and information obtained. The results of this study indicated that the Beji Sempuana site can be developed as a leading tourist attraction in Badung Regency, in addition to the natural beauty of the surroundings, the existence of cultural heritage objects and Beji Sempuana and religious ceremonies as tourist attractions. The buildings at Beji Sempuana and Pura Dalem Nataran are also unique with traditional Balinese architecture. This Beji Space pattern still applies the Tri Mandala Concept which is still preserved today.